UPAYA AUSTRALIAN AGENCY FOR INTERNATIONAL DEVELOPMENT (AUSAID) MELALUI PROGRAM BESIK II DALAM MENGATASI PERMASALAHAN AIR BERSIH DAN SANITASI DI TIMOR LESTE - Fasisaka, Idin; Suwecawangsa, Adi P.; Barreto Moniz, JosuÃ© Valentim (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2019)
ABSTRACT The Water, Sanitaion, and Hygiene (WASH) sector in Timor Leste is one of the number one domestic issue that continues to be improved through foreign assistance. One of the assistances came from AusAID which has been provided since 2002 through the Community Water and Sanitation Program which was then continued by the Rural and Sanitation Water or BESIK I and II programs in 2006 and 2012. In the BESIK II program, AusAID's focus was on technical issue by providing trainings for all levels of Timor Leste from the central government to the lowest level as a goal to utilize WASH infrastructures that was produced by the previous program and to improve the WASH sector in accordance with the targets of the Timor Leste Sustainable Development Goals. This study aims to describe the implementation of BESIK II towards that goal. This research was examined with the concept of program assistance and technical assistance. Using literature review techniques from sources and books related to the time with locus of research is from 2012-2016. Keywords: aid program, technical assistance, WASH, BESIK II